PARIETAL INTRADIPLOIC ENCEPHALOCELE IN AN ADULT : A RARE CASE - Dr. Harshvardhan Singh Rathore, Dr. Nilesh Ingale & Dr. Tulsi Manek (International Journal of Research Science and Management, 2019)
We report a rare case of parietal intradiploic encephalocele in a 51-year-old man presented to our hospital casualty with history of seizures, which was gradually progressive . The patient did not have anyprior history of head trauma. Intradiploic encephalocele is an extremely rare condition which consists of herniation of brain through openings of dura and skull. Intradiploic encephalocele is mostly seen in children with history of head trauma. Idiopathic intradiploic encephalocele has rarely been reported in adults.